2019
DOI: 10.1017/s0007114519002058
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of waist:height ratio on the association between BMI and frailty: the Korean Frailty and Aging Cohort Study

Abstract: Body weight is a major risk determinant of frailty, but the effect of obesity on frailty is controversial. The present study aimed to confirm the hypothesis that the risk of frailty is positively associated with obesity (BMI ≥ 30 kg/m2), but the association is mediated by the waist:height ratio (WHtR) in older women and men. A total of 2862 community-dwelling older individuals aged 70–84 years were assessed for frailty using the Korean version of Fatigue, Resistance, Ambulation, Illnesses, and Loss of weight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…Our findings are similar to those from previous cross-sectional [6,[11][12][13][14][15][16] and longitudinal [18][19][20][21][22][23][24][25] studies that demonstrated a U-or J-shaped relationship between BMI and frailty. Gajic-Veljanoski et al [41], using the Canadian Multi-Centre Osteoporosis Study, found that baseline BMIs �25 kg/m 2 was associated with faster frailty progression over 5-years with the greatest effect among those with BMI �40 kg/m 2 when compared to those with normal weight.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are similar to those from previous cross-sectional [6,[11][12][13][14][15][16] and longitudinal [18][19][20][21][22][23][24][25] studies that demonstrated a U-or J-shaped relationship between BMI and frailty. Gajic-Veljanoski et al [41], using the Canadian Multi-Centre Osteoporosis Study, found that baseline BMIs �25 kg/m 2 was associated with faster frailty progression over 5-years with the greatest effect among those with BMI �40 kg/m 2 when compared to those with normal weight.…”
Section: Discussionsupporting
confidence: 91%
“…Longitudinal studies have also found that obesity predicts the development of frailty [18][19][20][21][22][23][24][25]. For example, a study by Stenholm et al [24] concluded that midlife obesity led to a fivefold increase in the risk of frailty over a 22-year follow up compared to those of normal weight among participants in the Mini-Finland Health Examination Survey.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that malnutrition was associated with a substantially increased prevalence of frailty in the total sample and in both gender groups. The relation between malnutrition and frailty was already clearly established in previous studies, and overweight and obesity often co-exist with frailty [ 21 , 22 , 27 , 28 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 85%
“…Similar results were found in the Japanese cohort with a lowest incidence of frailty at a BMI between 21.4 and 25.7 kg/m 2 [ 22 ]. As shown by Kim et al, the risk of frailty is higher in obese women, which is mediated by WHTR, but not in obese men [ 28 ]. In Spain, two cohort studies showed a parallel change of abdominal obesity and BMI to be associated with an increasing risk of frailty [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation